Project Management in Construction: International Methodologies and Approaches for Ukraine’s Reconstruction - PETRUKHA, Nina; HROMYKA, Oleksii; KOKHAN, Marianna; KAMIENIEV, Oleksandr; DOROZHKO, Yevhen (International Journal of Contemporary Economics and Administrative Sciences, 2025)
The global construction industry is entering a transformative era, marked by the introduction of new technologies and sustainability requirements, as well as the expansion of the circle of stakeholders and their interests, allowing for improved connectivity and optimal processes of decision-making in planning and budgeting of the project. The right choice of methodologies and approaches in project management becomes a crucial factor in any construction project’ success. Thus, investigating current practices and trends of project management in construction becomes highly relevant task. Based on the method of bibliographic analysis, backed with the elements of grounded theory, the article presents an attempt to systematise current trends and challenges in the field of project management in construction, determined by the evolution of construction industry. The findings demonstrate the shift towards collaborative design and Agile paradigm in project management in construction, which enables overcoming challenging implications of fast dynamics of construction industry environment.